Syndromic Surveillance System for MERS-CoV as New Early Warning and Identification Approach [Corrigendum] - Salamatbakhsh M; Mobaraki K; Ahmadzadeh J (Dove Medical Press, 2020)
Salamatbakhsh M, Mobaraki K, Ahmadzadeh J. Risk Manag Healthc Policy. 2020;13:93– 95.The authors have advised that the date shown on page 93, main text, line 5 “ 23.09.2017 to 26.07.2019” should read “ 23.09.2012 to 26.07.2019”. The authors apologize for this error.Read the original article